Vitamin D Intake among Premenopausal Women Living in Jeddah: Food Sources and Relationship to Demographic Factors and Bone Health - Tahani A. Zareef; Robert T. Jackson; Abdulkareem A. Alkahtani (Journal of Nutrition and Metabolism)
Background. Saudi women depend on food sources to maintain their serum 25(OH) D concentrations because covering by traditional clothing and time spent indoors limit their sun exposure. Little is known about vitamin D intake and its main food sources in Saudi Arabia. In addition, the association between vitamin D and calcium intake and bone mineral density (BMD) in young women is not well researched. Objectives. To assess the adequacy of vitamin D intake among Saudi women as compared to the estimated average requirements (EARs), to identify dietary vitamin D sources, to examine potential determinants of vitamin D intake, and to assess bone health and the association of calcium and vitamin D intake with BMD. Methods. This cross-sectional study was conducted in 257 premenopausal women aged 20–50 years in Jeddah, Saudi Arabia. Dietary vitamin D and calcium were assessed by the Semiquantitative Food Frequency Questionnaire. BMD was measured using dual-energy X-ray absorptiometry (DXA) in a subset of women n=102 at the lumbar spine and femur neck. Results. Sixty-five percent of women were below the EAR for vitamin D, and 61% fell below the EAR for calcium. Dairy products, supplements, and fish contributed most to vitamin D intake. Increased age was an independent determinant of sufficient vitamin D intake p<0.001. The prevalence of osteopenia was 33% in the lumbar spine and 30% in the femur neck. There was a significant positive association between calcium intake and BMD at the lumbar spine p=0.043 after controlling for body mass index and energy intake. Vitamin D intake was not significantly different between women with low and normal bone mass. Conclusion. Premenopausal women in Jeddah have insufficient vitamin D and calcium intakes. Public health strategies to improve nutrition in young women are needed, and expanding fortification programs to include all dairy products would be useful.